4-aminobenzylphosphonic acid-modified glassy carbon electrode for electrochemically sensing paracetamol - Yang, Guocheng (2014)
4-Aminobenzylphosphonic acid (4-ABPA) was covalently immobilized on a glassy carbon electrode (GCE) surface via an electrochemical oxidation process. The bare and 4-ABPA-modified GCEs were employed to sense paracetamol (PCT) in a series of buffer solutions with different pH values at 36.8 C for comparison. The results showed that the 4-ABPA-modified GCE was more stable with higher electrochemical sensitivity toward PCT than the unmodified one. Moreover, the 4-ABPA-modified GCE can be used to monitor in-vitro dissolution process of PCT-loaded electrospun poly(vinyl alcohol) (PVA) nanofiber systems in real time.